Social Media Seeps into Pakistani Madrasas: Exploring Usage Patterns of Seminary Students Darul Uloom Haqqania-Pakistan - Dr. Babar Hussain Shah,; Saqib Riaz,; Sana Rashid,; Shahzada khan Mohmand, (Journal of Peace, Development and Communication, 2021)
Interacting with friends & families over long distances to express feelings and thoughts has been among basic needs for human beings since the creation of this universe. Throughout history, people have continuously trusted in communication to strengthen their contacts. The arrival media either print, electronic or social media has provided a greater impetus to human communication. This study is also an effort to explore the social media usage among seminary students. Though in Pakistan it is not convenient to access Madrasa students yet researcher through purposive sampling access the students. When contacted 150 students expressed their consent to participate in the survey. However, finally 122 students were able to fill in the questionnaire. Results indicate that majority of the respondents (95%) use Facebook, while usage of WhatsApp consisted of 109 students of the Madrasa. Usage of other social media platforms like Imo and YouTube comprised of only 5 students. When patterns of usage were explored it was found that 41% respondents used social media on daily basis. It was found that 9 percent of the respondents used social media more than ten hours in a week. Findings also shows that most of the respondents (69%) use social media for seeking information, 41% use for entertainment, 56% use for communicating with family and friends, 14% use for publication of Islam (which is shocking find though) and 49% respondents use social media for passing time.